Isotretinoin 5 mg daily for low‐grade adult acne vulgaris – a placebo‐controlled, randomized double‐blind study. (26th April 2013) - Rademaker, M.; Wishart, J.M.; Birchall, N.M.
Abstract Background Despite acne persisting into adulthood in up to 50% of the population, very few therapeutic studies have been performed in this age group. Objectives To assess the efficacy of 5 mg/day isotretinoin in adult acne. Methods An investigator initiated, industry‐sponsored, randomized, double‐blind, placebo‐controlled, parallel‐group clinical study of isotretinoin 5 mg/day in the treatment of low‐grade adult acne for 16 weeks followed by an open‐label phase of 16 weeks. Group 1 received 32 weeks of 5 mg isotretinoin/day; Group 2 first received 16 weeks of placebo, followed by 16 weeks open‐label 5 mg isotretinoin/day. Patients were followed for a further 10 weeks off treatment. The primary end‐point was the difference in acne lesion count and disability score after 16 weeks isotretinoin compared to placebo. Secondary end‐points included differences in these counts/scores after 32 weeks of isotretinoin compared to baseline, and after 10 weeks off treatment, compared to end of treatment (week 32). Results There were highly significant differences (P < 0.0001) in acne lesion count, Dermatology Life Quality Index and self‐assessment after 16 weeks of isotretinoin, compared to placebo (both per protocol and intention to treat). Acne lesions fell significantly, within 4 weeks of 5 mg isotretinoin/day (Group 1) and continued to fall during 32 weeks of treatment [acne lesion count (mean ± SD): 11.3 ± 8.1 (baseline), 3.6 ± 5.5 (week 16), 1.3 ± 3.1 (week 32), P < 0.0001)]. There was a similar significant reduction in acne lesion count in Group 2, but only from week 20, 4 weeks after starting open‐label 5 mg isotretinoin. Adverse effects were minimal. Conclusions Isotretinoin 5 mg/day is effective in reducing the number of acne lesions, and improving patients dermatologic quality of life, with minimal adverse effects.